Preventive and corrective maintenance – cost comparison and cost–benefit analysis. Issue 5 (3rd May 2016) - Stenström, Christer; Norrbin, Per; Parida, Aditya; Kumar, Uday
Abstract : Maintenance can represent a significant portion of the cost in asset intensive organisations, as breakdowns have an impact on the capacity, quality and cost of operation. However, the formulation of a maintenance strategy depends on a number of factors, including the cost of down time, reliability characteristics and redundancy of assets. Consequently, the balance between preventive maintenance (PM) and corrective maintenance (CM) for minimising costs varies between organisations and assets. Nevertheless, there are some rules of thumb on the balance between PM and CM, such as the 80/20 rule. Studies on the relationship between PM and CM in practice are rare. Therefore, PM and CM costs are studied in this article by analysing historical maintenance data. A case study of rail infrastructure historical data is carried out to determine the shares of PM and CM, together with a cost–benefit analysis (CBA) to assess the value of PM. The results show that the PM represents 10% to 30% of the total maintenance cost when user costs, i.e. train delays, are included as a CM cost. The CBA shows the benefit of PM is positive with a benefit–cost ratio at 3.3. However, the results depend on the inclusion/exclusion of user costs, besides individual organisational parameters.